Adalimumab, therapeutic alternative in the Vogt Koyanagi Harada syndrome refractory to infliximab: case report - Moya Ayre, Eugenio Franklin (2016)
Vogt Koyanagi Harada syndrome (VKH) is a bilateral panuveitis included in the uveomeningeal syndromes. Treatment of its chronic stage is difficult because of poor response to mmunomodulation. Other therapeutic options include biological agents such as anti-TNF alpha. We present the case of a patient with severe VKH resistant to infliximab that responded to adalimumab. Adalimumab is a humanized monoclonal antibody effective when there is resistance to infliximab in patients with chronic persistent VKH syndrome. The case presented is interesting because of uncommon resistance to this drug in the clinical practice; the use of tissue plasminogen activator contributed significantly to visual improvement.